Urticaria and mimickers of urticaria - Fok, Jie Shen; Katelaris, Constance H. (Frontiers in Allergy, 2023)
UrOcaria is a common skin condiOon encountered across various specialOes in medicine, especially in dermatology and allergy/immunology pracOce. It has a heterogeneous presentaOon hence it is unsurprising that many skin condiOons may be confused with urOcaria. UrOcaria may present as acute or chronic urOcaria, the laPer can be further categorised as chronic spontaneous and chronic inducible forms. In this arOcle, we explore, explain, and summarise various skin lesions that are considered mimickers of urOcaria, with the aim to promote understanding of each of the condiOons highlighted, to improve recogniOon and to reduce misdiagnosis.